Syndrome-Fortuna: A viable approach for Linux random number generation - Campos, Sérgio Vale Aguiar; van de Graaf, Jeroen; Silveira, Daniel Rezende (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2011)
This work presents a random number generator based on the intractability of an NP-Complete problem from the area of error-correcting codes. It uses a non-heuristic approach for entropy collection, taken from the Fortuna design philosophy. We implemented the new generator inside the Linux kernel, providing an alternative system interface for secure random number generation.